Potential of adventure body practices as content for school physical education in a remaining quilombo community (Revista Contexto & Educação, 2025)
The adventure body practices are part of the Physical Education curriculum component and should be applied in classes from the later years of Elementary School to the third year of High School, according to the National Common Curricular Base document. In light of this, the main objective of the study is to analyze the possibility of using adventure body practices as content for school Physical Education. The research is of an applied nature, with an exploratory and descriptive objective, employing a qualitative approach. The study was conducted through a questionnaire with students from 6th to 9th grade of elementary school. Based on the information obtained from the questionnaire, it was observed that there is a lack of knowledge and use of adventure body practices in the school environment. The research also indicates as a result that adventure body practices can and should be taught as school content in Physical Education classes, as the school is located in an easily accessible environment for students, with an extensive area of forest and streams that allow the use of various activities in this category. Furthermore, there is a noticeable interest among students in gaining knowledge and experience in innovative activities.
Keywords: Content; Physical Education; Adventure Body Practices; Remaining Quilombo Communities